Experiments in freedom : representations of identity in new South African drama : an investigation into identity formations in some post-apartheid play-texts published in English by South African writers, from 1994 - 2007 - Hagemann, Fredrick (University of Pretoria, 2013)
Thesis (DLitt)--University of Pretoria, 2008.